Sediment dynamics in shallow water under wave-current interaction: a case study of Haiyang Beach - Yu, Yue; Sun, Hongan; Liu, Xingmin; Qiao, Lulu; Wang, Yongzhi (Frontiers in Marine Science, 2025)
As a critical interface in coastal systems, the intertidal zone presents complex sediment dynamics, yet the precise mechanisms governing resuspension and transport under combined wave-current interactions are not fully resolved. Utilize a comprehensive observation system that incorporates both acoustic and optical equipment, we captured concurrent hydrodynamic and sediment data across a full tidal cycle. By applying wave-turbulence decomposition, we successfully isolated the distinct contributions of various forcing mechanisms. Our results unequivocally demonstrate that turbulence is the primary driver of sediment resuspension, superseding the effects of direct wave orbital motion and mean current shear, as confirmed through both regression and wavelet analyses. Moreover, we distinguish between local and net processes: while resuspension is a locally forced phenomenon, net sediment transport is governed by the mean flow. During our observations, the net cross-shore transport was persistently offshore, driven by the combination of ebb tidal currents and wave-induced undertow. Ultimately, these findings challenge the paradigm of wave-dominated sediment processes on tidal flats, underscoring the pivotal role of turbulence in modulating sediment dynamics and offering a more refined perspective on the local sediment budget.